Implantación de un sistema contable en el local comercial “Zona Auto Erazo” de la ciudad de Yantzaza periodo enero –marzo del 2016 - Medina Salinas, Jenny Amparito (2017)
Currently due to the increase in business and the advances in technology, it is necessary to establish an accounting system in the commercial "Zone Auto Erazo", so that the business maintains an effective and effective control of each of its activities; In the same way it will be achieved a use in the use of the available resources, obtaining the fulfillment of the objectives raised in the business; As a result of the application of the accounting system, the elaboration of the Financial Statements based on them, the owner will make the best decisions for the benefit of the commercial premises; Finally, it should be mentioned that this research work is carried out prior to choosing the degree of Accounting and Auditing Engineering, under the regulations of the National University of Loja. In the present thesis research, the development of the proposed objectives through the Implementation of an Accounting System in the commercial premises was accomplished, its development is oriented to present in detail the Commercial Accounting in accordance with the current Accounting Regulations, The development of the Initial Inventory, State of Initial Situation through which we can know the total assets of the company, as well as its obligations. Preparation of the Plan and Manual of Accounts for the registration of the entire accounting process, starting from Daily Book, until the presentation of the Financial Statements. Concluding that the accounting system is an optimal, efficient and effective tool at the time of decision making, investment, control of expenses, control of the merchandise account among other aspects that guarantee the control of business activities.